Programs, Proofs, Processes 6th Conference on Computability in Europe, CiE 2010, Ponta Delgada, Azores, Portugal, June 30 <U+0013> July 4, 2010. Proceedings - Ferreira, Fernando.; Lw̲e, Benedikt.; Mayordomo, Elvira.; Mendes Gomes, Lus̕. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 6th Conference on Computability in Europe, CiE 2010, held in Ponta Delgada, Azores, Portugal, in June/July 2010. The 28 revised papers presented together with 20 invited lectures were carefully reviewed and selected from 90 submissions. The papers address not only the more established lines of research of computational complexity and the interplay between proofs and computation, but also novel views that rely on physical and biological processes and models to find new ways of tackling computations and improving their efficiency.